Geolocator tagging reveals Pacific migration of Red‐necked Phalarope Phalaropus lobatus breeding in Scotland. (20th August 2014) - Smith, Malcolm; Bolton, Mark; Okill, David J.; Summers, Ron W.; Ellis, Pete; Liechti, Felix; Wilson, Jeremy D.; Pearce‐Higgins, James
<x xml:space="preserve">Abstract</x> The migration route of Red‐necked Phalarope populations breeding on North Atlantic islands has been subject to considerable speculation. Geolocator tags were fitted to nine Red‐necked Phalaropes breeding in northern Scotland to assess whether they migrated to Palaearctic or Nearctic wintering grounds. Of four birds known to return, two had retained their tags, of which one was recaptured. This male Phalarope left Shetland on 1 August 2012 and crossed the Atlantic Ocean to the Labrador Sea off eastern Canada in 6 days, then moved south to reach Florida during September, crossed the Gulf of Mexico into the Pacific Ocean and reached an area between the Galapagos Islands and the South American coast by mid‐October, where it remained until the end of April, returning by a similar route until the tag battery failed as the bird was crossing the Atlantic Ocean. The total migration of 22 000 km is approximately 60% longer than the previously assumed route to the western part of the Arabian Sea, and this first evidence of migration of a European breeding bird to the Pacific Ocean also helps to indicate the possible migratory route of the large autumn movements of Red‐necked Phalaropes down the east coast of North America.